Analisis Kinerja Keuangan Pada PT. Nippon Corpindo Indosari Tbk - Zaqiatul Qalbi; Sabirin Sabirin; Khairina Khairina (Jurnal Kajian dan Penelitian Umum, 2023)
This research aims to determine the financial performance of PT. Nippon Indosari Corpindo Tbk for the 2020-2022 period which is listed on the Indonesia Stock Exchange (BEI). The object of this research is the Indonesian stock exchange PT Nippon Indosari Corpindo for the 2020-2022 period. The research data used is secondary data whose sampling method uses non-probability sampling. And the data analysis method is by calculating financial ratios, drawing conclusions, while the sample taken is the profit and loss of PT Nippon Indosari Corpindo. The results of this research show that the liquidity ratio is measured by the cash ratio and cash ratio, the overall condition of the company is in good condition, the Solvency Ratio is measured by DAR, the condition of the company is not good, while the DER is not good, the profitability ratio is measured by GPM and NPM in overall condition. the company is in good condition. The activity ratio is measured by total asset turnover and fixed asset turnover. Overall the company is in good condition.